Identificating subject of the operational control - Ліпич, Любов Григорівна; Lipych, Liubov H.; Мельник, Катерина Петрівна; Melnyk, Kateryna P.; Шматковська, Тетяна Олександрівна; Shmatkovska, Tetiana O.; Матвійчук, Наталія Миколаївна; Matviivhuk, Nataliia M. (Державний вищий навчальний заклад “Університет банківської справи”, Харківський навчально-науковий інститут, 2017)
The article studied in details the basis of the theory of control, the necessity of determining the subject for further development of science and effective control activity in practice. Critical analysis of the fundamental works of accounting and control revealed the limits of the domain of operational control. It was found out that the object determines the scope of operational control, the conditions and the state of its operation mechanism. The components of the subject of operational control are interrelated, allowing one to find a way to achieve its objective and qualitative tasks. Proved that its subject is a special part of the theory, which describes in details the nature and breadth of operational process control to adapt its organization and methods to the specific conditions of the enterprise. The practical significance of operational control reveals due to the subject, which is manifested in the constant impact of the subject of control (control component) on its object (driven component) through the techniques, methods and tools (methodological component), which ensure smooth and efficient operation of all structural divisions, by avoiding or quickly correcting mistakes, shortcomings and negative effects of the economic process. In the article the authors provide substantiation of interrelationship of operative control and economic security of the enterprise. In the publication determined, that in the realities of the present well organized operational control creates the preconditions for ensuring economic and financial security.
Ідентифікація предмету оперативного контролю
Keywords: оперативний контроль; operational control; предмет; subject; теорія; theory; система управління; management system; категорія; category; інформація; informatoin; економічна безпека; economic security